Deep Electrical Resistivity Tomography for the Hydrogeological Setting of Muro Lucano Mounts Aquifer (Basilicata, Southern Italy). (27th February 2019) - Rizzo, E.; Giampaolo, V.; Capozzoli, L.; Grimaldi, S.
Abstract : The proposed work concerns the application of a deep geoelectrical survey to a carbonate aquifer in order to define the best location for exploitation well drilling for increasing water supply. However, an optimal characterization of a groundwater resource is the necessary condition to reach the indicated aim. Therefore, the geoelectrical investigation was guided from the previous geological and hydrogeological characterization. Moreover, geophysical methods are good tools to improve the groundwater model when detailed information is necessary, such as the localization of a pumping well. The work summarizes the hydrogeological knowledge at the West of the Basilicata Region (Muro Lucano, Italy). The investigated area is characterized by the presence of a karst aquifer which is made up of a carbonate ridge (Castelgrande, Muro Lucano) that tectonically dips southward and is widely covered by Pliocene deposits (sands and conglomerates), by the Irpinian unit and Sicilide unit formations, and by debris slope and landslide deposits. The assessment of the complex hydrogeological framework of the area was detailed by the use of a new multichannel deep geoelectrical technique (DERT). In details, the proposed technique was able to successfully locate a less resistive zone connected to a more fractured limestone and then it was suitable for the localization of a groundwater exploitation well.